Students’ Perception of English Studies Use the Google Meet Application at The Tenth Grade of Senior High School Number 3 Jambi City - Meiliza Delviyanti; Yanti Ismiyati; Ridho Praja Dinata (JELT: Journal of English Language Teaching, 2022)
This study aims to determine students' perceptions of using the Google Meet application for learning English in class X SMA Negeri 3 Jambi City. Because we know, the covid-19 has hampered all activities outside the home, one of which school being carried out online. The research methodology in this study is qualitative research design whose analysis requires in-depth observation. The subjects in this study were students of class X MIPA 2 SMAN 3 Jambi City, was used purposive sampling totaling 6 students as participants consisting of two students from low scores, two students from medium scores and two students from high scores.. In collecting data, this research gave interviews in class. The results showed that class X students of SMA Negeri 3 Jambi City had network difficulties in learning English using the Google Meet application, however, students also found it easier to learn English using the Google Meet application because of the flexible time and being able to find their most comfortable place in language learning English. Google meet application can be implemented went the teacher wants to teach material, can share the screen with students to show the learning material. Sometimes the teacher also gives time for students to interact in the meeting room such as conversations, dramas and so on.